Changes in residual stresses caused by an interruption in the weld process of ships and offshore structures. (3rd April 2017) - Kenno, Sara Y.; Das, Sreekanta; Rogge, Ronald B.; Gharghouri, Michael A.
Abstract : Residual stresses are present in welded stiffened steel plates that are used to construct ships and other offshore structures. These locked-in stresses can exceed the yield stress of the parent plate material. Interruptions due to stop and restart in the welding process in these structures cannot be eliminated completely. It is suspected that weld interruptions are detrimental, though the effect of an interruption on the residual stress distribution is not well understood. Hence, this study was undertaken to determine the change in the residual stresses due to various stop durations in the weld process. The stop time varied from 10 to 60 seconds and the resulting stresses were compared with those observed when the weld is not interrupted. Neutron diffraction was used to determine the residual stresses. The study revealed that, compared to the residual stresses observed for a continuous weld, immediately before the stop location there is a decrease in the resulting residual stresses which is balanced by a concomitant increase immediately following the restart of the weld. The difference between the low and the high stress points in the distribution increased as the stoppage time (duration) increased. This paper presents the specimen design, specimen preparation and construction, test method, and test data obtained for four steel plate specimens.